A Low FODMAP Diet May Reduce Symptoms in Patients With Fecal Incontinence. Issue 7 (July 2019) - Menees, Stacy B.; Chandhrasekhar, Deepa; Liew, Ee Lane; Chey, William D.
Abstract : INTRODUCTION: Fecal incontinence (FI) is a common complaint and is often associated with diarrhea and urgency. Foods high in fermentable oligo-, di-, and mono-saccharides and polyols (FODMAP) cause symptoms of diarrhea and urgency. Therefore, this study assesses the impact of a low FODMAP diet on the occurrence of FI due to loose stool. METHODS: This study is a retrospective chart review of patients with FI seen in the Michigan Bowel Control Program clinic between August 2012 and December 2017. Patients who had FI with loose stool without red flag signs and who were recommended a low FODMAP diet and underwent formal dietary instruction with a Michigan Medicine dietician were included. RESULTS: Sixty-five patients with FI who underwent formal dietary teaching were included in this study. Eighty-eight percent of the patients were white, and 87% were women with a mean age of 62 years (±14 years). Additionally, the chart review showed that 35% of the patients had FI daily, 21.5% had FI weekly, and 5% had FI monthly. About 64.6% of the patients (42) had reported a reduction in their FI symptoms with the low FODMAP diet. There was no demographic or clinical characteristic that predicted the response to a low FODMAP diet. DISCUSSION: In this case series, dietary manipulation with a low FODMAP diet was a useful tool to treat patients who suffer from FI due to loose stool. Further confirmatory, prospective randomized controlled trials are required to see the true efficacy of a low FODMAP diet in patients who suffer with FI.